Abdominal perfusion in canine patients with pyometra and sepsis evaluated by Doppler and contrast-enhanced ultrasound - Beatriz Gasser; Ricardo Andres Ramirez Uscategui; Luiz Paulo Nogueira Aires; Diego Iwao Yamada; Priscila Del’Aguila-Silva; Bruna Bressianini Lima; Priscila Silva; Igor Cezar Kniphoff da Cruz; Rafael Kretzer Carneiro; Marcus Antônio Rossi Feliciano (BMC Veterinary Research, 2023)
Abstract Background Sepsis is a condition characterized by organic dysfunction, leading to hemodynamic instability and high morbidity and mortality rates in humans and animals. Early identification of perfusion changes and appropriate management of sepsis are crucial for improving patient prognosis. Currently, the Systemic Inflammatory Response Syndrome (SIRS) and Sequential Organ Failure Assessment (SOFA) scores are widely studied for sepsis identification and evaluation of organ dysfunction. However, these scores do not assess gastrointestinal involvement, which is common in this condition. Contrast-enhanced ultrasound (CEUS) and Doppler have been considered promising diagnostic techniques for detecting changes in vascularization and microcirculation in a non-invasive and safe manner, particularly in the gastrointestinal system. This study aimed to evaluate duodenal perfusion using CEUS, as well as abdominal aortic and cranial mesenteric artery blood flow using Doppler ultrasound, and systolic arterial pressure (SAP) in 17 bitches with pyometra and in 10 healthy animals. Results The variables were compared between the pyometra and control groups, as well between patients with and without sepsis determined by the SOFA or SIRS scores. Pyometra was found to cause a reduction in abdominal aortic blood flow volume, aortic peak systolic velocity, and resistivity index as evaluated by Doppler ultrasound. Patients with sepsis according to the SOFA criteria only presented lower SAP. In contrast, sepsis animals identified by the SIRS score exhibited lower SAP, aortic peak systolic velocity, aortic blood flow volume, and aortic resistivity index and additionally, higher peak intensity of contrast in the duodenal wall. Conclusions Pyometra causes a reduction in abdominal aortic blood flow, which is more pronounced in animals with sepsis identified by the SIRS criteria. These animals also exhibited a decrease in systolic blood pressure and an increase in duodenal perfusion, as evident by CEUS. However, these changes were not observed in patients with sepsis identified by the SOFA criteria. The alterations in intestinal perfusion observed in animals with sepsis indicate the presence of inflammation or dysfunction. In this regard, CEUS proves to be a valuable technique for detecting subtle changes in tissue hemodynamics that may not be apparent in conventional exams.